Improving English Listening Skills for Vocational Students Through Interactive ICT Tools - Muhammad Husaein Jaya Negara; Jamilah (Universitas Islam Negeri Palopo, 2025)
Vocational students often face difficulties in developing English listening skills, particularly with authentic speech that includes varied accents, fast delivery, and technical terms. This Classroom Action Research conducted at SMK N 2 Depok explored the use of interactive ICT tools—YouTube and ESLVideo.com—to enhance listening comprehension among 36 eleventh-grade Computer and Network Engineering students. The intervention applied a Genre-Based Approach in two cycles, using authentic YouTube videos for exposure to real-world discourse and ESLVideo.com quizzes for interactive practice with immediate feedback. Data from tests, observations, and interviews showed substantial progress: students’ mean listening scores increased from 71.25 to 90.83, accompanied by higher engagement and confidence. Qualitative findings revealed that visual and verbal integration reduced comprehension difficulty and motivated students to participate more actively. Despite challenges such as technical issues and classroom management, reflective adjustments helped maintain consistent improvement. The study concludes that integrating interactive ICT tools can effectively enhance vocational students’ listening competence and foster independent learning aligned with professional communication needs.